QUALITY MANAGEMENT EDUCATION PROFILE: RATING EVALUATION - Stoikova, Victoriia V. (Educological discourse, 2017)
The introduction of Profile education is accompanied by a number of problems that are clearly determined at the regional level. This article describes the mechanisms to identify these problems and shown the most effective ways to control the quality of specialized education in the regional educational system which is based on the rating evaluation. The author has proposed a system of criteria for the construction of rating the quality of Profile education which is combined into three equal areas: the ensuring organizational and pedagogical conditions of implementation of Profile education at general education institutions; the introduction of network forms of organization of Profile education; the effectiveness of Profile education. The author's methodology of calculation the quality criteria of Profile education has been presented in the article. The ponderability of the criteria has been determined by peer review.